Methanolic Extract of Winter Cherry Causes Morpho-Histological and Immunological Ailments in Mulberry Pyralid Glyphodes pyloalis - Afraze, Zahra; Sendi, Jalal J.; Karimi-Malati, Azadeh; Zibaee, Arash (Frontiers in Physiology, 2020)
Abstract The effect of Withania somnifera a medicinal plant seed extract was tested against lesser mulberry pyralid, a potential pest of mulberry. The mulberry leaves were used for silk production in rural areas of northern Iran. The extract was administered orally by leaf dipping method in two lower (5 %W/V) and higher (15%W/V) dosages to third instar larvae (<24 h) for biological assays and to fifth instar larvae (<24 h) for Physiological studies. The results showed formation of larvoids (Ls), larval-pupal intermediates (LPIs), pupoids (Ps) and pupal-adult intermediates (PAIs). The results showed increased larval duration by 1.7 and 2 folds in 5 and 15 % treatment respectively. Fecundity of resultant adults was decreased by 1.2 and 1.3 in 5 and 15 % treatment respectively. Except approximate digestibility (AD) and consumption index (CI) all other feeding indices showed reduction. The feeding deterrence was prominent at 15 % (87 %) and 5% showing 48 % deterrence. Our enzymatic and non-enzymatic assessments upon treatment showed reduction in key components, except detoxifying enzymes. However, the activity of an important enzyme involved in cuticle hardening and immunity called phenoloxidase was reduced. We also investigated the histology of midgut for further analysis and found drastic changes in main cellular elements. Immunological changes following treatment was noticeable in reduced Total Hemocyte Count but surprisingly increased Differential Hemocyte Count. However, the hemocytes structure was extremely damaged. The reduced number of eggs in treated but survived adults indicated reduced ovaries, with vacuolization both in trophocytes and oocytes. The key chemical compounds showed reductions particularly at 15%. The present results are concomitant with few earlier studies on this medicinal plant and deserve further studies particularly in deriving key chemicals that alter metamorphosis similar to insect growth regulators.